Intravenous Administration of Human Adipose Derived-Mesenchymal Stem Cells Is Not Efficient in Diabetic or Hypertensive Mice Subjected to Focal Cerebral Ischemia - Mangin, Gabrielle; Cogo, Adrien; Moisan, Anaïck; Bonnin, Philippe; Maïer, Benjamin; Kubis, Nathalie; , on behalf of the RESSTORE Consortium (Frontiers in Neuroscience, 2019)
As the third cause of death and cognitive decline in industrialized countries, stroke is a major burden for society. Vascular risks factors such as hypertension and diabetes are involved in most stroke patients, aggravate stroke severity, but are still poorly taken into account in preclinical studies. Microangiopathy and sustained inflammation are exacerbated, likely explaining the severity of stroke in those patients. We sought to demonstrate that intravenous administration of human adipose derived-mesenchymal stem cells (hADMSC) that have immunomodulatory properties, could accelerate sensorimotor recovery, prevent long-term spatial memory and promote neurogenesis, in diabetic or hypertensive mice subjected to permanent middle cerebral artery occlusion (pMCAo). Diabetic (streptozotocin IP) or hypertensive (L-NAME per os) male C57Bl6 mice subjected to pMCAo, were treated by hADMSC (500,000 cells IV) 2 days post stroke. Infarct volume, neurogenesis microglial/macrophage density, T-lymphocytes density, astrocytes density and vessel density were monitored 7 days after cells injection and at 6 weeks. Neurological sensorimotor deficit and spatial memory were assessed until six weeks post stroke. Whatever the vascular risk factor, hADMSC showed no effect on functional recovery/cognitive decline prevention at short or long-term assessment, nor significantly modified neurogenesis microglial/macrophage, T-lymphocytes, astrocytes and vessel density. This work is part of a European program (H2020, RESSTORE). We discuss the discrepancy of our results with those obtained in rats and the importance of timing, source and type of cells according to the species that is considered. A comprehensive understanding of the mechanisms preventing recovery should help for successful clinical translation but first could allow identifying good and bad responders to cell therapy in stroke.